Synthesis and Evaluation of Antibacterial and Antifungal profile of some Newer Isoxazole Analogous (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
A new series of 5-(chloromethyl)-3- (substituted phenyl) isoxazole was synthesized in the presence of sodium hydroxide, substituted aromatic aldehyde (1) combine to produce oxime(2), which are then cyclized in the presence of dichloromethane, triethylamine, & N-chlorosuccinimide to develop Compound (3) and on chlorination onward 5-(chloromethyl)-3- (substituted phenyl) isoxazole (4). By employing IR, 1H-NMR, mass spectral, and elemental analyses, the chemical compositions of the generated molecules were verified. The developed molecules were tested for their antibacterial properties (E. coli & S. aureus), antifungal (A. niger & C. albicans). The new compound demonstrated considerable antibacterial and antifungal activity on level with standards set.